2023
DOI: 10.31989/ffhd.v13i2.1050
|View full text |Cite
|
Sign up to set email alerts
|

Interim report from a 2-year double-blind rct testing fermented papaya preparation on immune enhancement, endothelial health and qol in elderly adults

Abstract: Background: Agingis associated with alterations in oxi-inflammatory-immune profile, and endothelial cell dysfunction. Indeed, increased generation of free radicals as well as immunosenescence are hallmarks of the aging process and age-related diseases. In the past 12 years or so, data has been accumulated on fermented papaya preparation (FPP®)(Osato Research Institute, Gifu, Japan), a specific functional food with robust redox and immune regulator nutrigenomics effect. The aim of this 2-year ongoing study of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Some studies on chronic degenerative diseases such as thalassemia, cirrhosis, diabetes as well as aging have shown that FPP can act favorably on the immune and vascular systems through an anti-inflammatory action and a modification of the biomarkers of oxidative stress damage [59][60][61][62]. For these positive direct and indirect effects on health, FPP is considered a functional food [63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on chronic degenerative diseases such as thalassemia, cirrhosis, diabetes as well as aging have shown that FPP can act favorably on the immune and vascular systems through an anti-inflammatory action and a modification of the biomarkers of oxidative stress damage [59][60][61][62]. For these positive direct and indirect effects on health, FPP is considered a functional food [63][64].…”
Section: Discussionmentioning
confidence: 99%
“…For the last 13 years, a proprietary functional food known as fermented papaya preparation (FPP®, Osato Research Institute, Gifu, Japan, Patent Number: 6401792) has undergone rigorous validation through numerous experimental and clinical trials, showcasing its enduring immune and redox modulator nutrigenomics effects [1][2][3][4][5][6].The Functional Food Center's (FFC) recent consensus has provided a distinct and enhanced definition for evidence-based functional foods, elucidating their impactful bioactivity and the associated biomarkers [7].This year a brief but stringent position paper further focused on the fundamental regulatory pillars in the field [8]. In the previously published 1-year preliminary report [9] of the present 2-year investigation, we demonstrated that, as compared to the antioxidant-mix supplementation, FPP ® intervention significantly decreased the asymmetric dimethylarginine (ADMA), an endogenous NOS inhibitor and the percentage of apoptotic PBMC, together with a more satisfactory quality of life profile in middle-age/elderly subjects. On the other hand, the dynamics of other variables such as neutrophil lymphocyte ratio (NLR) values, no matter the treatment group, did not reach substantial differences.…”
Section: Introductionmentioning
confidence: 99%
“…Since cGMP is excreted through urine, measuring the levels of urinary nitrates Functional Foods in Health and Disease 2023; 13 (6):307-319 and cGMP is a suitable and non-invasive method for assessing NO. Asymmetric dimethylarginine (ADMA) is widely recognized as the inhibitor of NO production by competing for the binding with arginine and NO synthase (NOS) [6][7]. Therefore, the ratio of arginine/ADMA (substrate/inhibitor ratio) may predict NO production better than ADMA or arginine concentrations alone [8].…”
Section: Introductionmentioning
confidence: 99%